Authority Of Notary In Making Related Act With Land In The Context Of Land Registration Under Paragraph 2 Of Article 15 Of Notary Law - Argo Suseno; Sema Ardianto; Amin Purnawan (Jurnal Akta, 2018)
Notaries in making written evidence in the form of an authentic act, done according to the will of the parties / party attended for otherwise in agreement and in front, so as not to violate the law, and that the will of the parties is done properly and correctly. The aim of this study was to  know implementation notary authority in the said agreement to land in the context of land registration in accordance with Article 15 paragraph 2 of Notary law, as well as to find out the barriers and solutions in the implementation of the authority. The method is carried out normative, descriptive specification using secondary data, through literature, then analyzed qualitatively. The results show that (1) the exercise of authority notarized in agreement a blessing to the land in the context of land registration in accordance with Article 15 paragraph 2 of Notary law is done according to the code of ethics of notaries authorized to make the Agreement of Waiver or agreement of transfer of right, obstacles encountered is community refusal to act because of the cost factor and solutions in the implementation of the authority having socialization law on public notary's role in making the act in the context of land registration.Keywords: Notary, Authentic Documents, The Land Registry.